Local Wisdom as Mechanism for Religious Pluralism: A Socio-Cultural Study of Banjarpanepen Village in Azyumardi Azra's Perspective - Huda, Ulul; Suparjo, Suparjo; Sugiarti, Iis; Bakhit, Mohammed Elfadil Ahmed (Institut Agama Islam Negeri (IAIN) Manado, 2025)
Religious pluralism in multi-religious communities requires effective social mechanisms to maintain harmony. This study examines how local wisdom functions as an operational mechanism of religious pluralism in Banjarpanepen Village, a multi-religious community in Banyumas, Central Java, through Azyumardi Azra's socio-cultural perspective. This qualitative case study was conducted over four months in 2025 using semi-structured interviews, participant observation, and documentation. Informants were selected through purposive sampling representing diverse religious backgrounds (Islam, Christianity, Buddhism, and Belief Adherents), including religious leaders, customary elders, village officials, and active community members. Data were analyzed using Miles and Huberman's technique, with validity enhanced through triangulation. Local wisdom practices) including Grebeg Suran, Purnamaan, Nyadran, and Slametan (function as operational mechanisms that strengthen interfaith harmony, regulate social interactions, and build community solidarity. Religious leaders, customary elders, and village officials play complementary roles in maintaining harmony through both formal and informal networks. Banyumasan cultural values of nrimo and respect for others provide the ethical foundation for peaceful coexistence. Findings validate Azra's framework of moderation, cultural openness, and socio-religious networks, demonstrating that Nusantara Islam pluralism is not merely normative discourse but lived through adaptive and inclusive daily social practices, positioning village pluralism as a practical expression of institutionalized cultural harmony.